A study of the information needs and information-seeking behaviour of students in the Chinese High School, Singapore - Ang, Rosalind Mei Kway (2008)
This paper was primarily concerned with identifying the information needs and information-seeking behaviour of the students in The Chinese High School with the aim of improving the collection of resources and services offered by the school media resource library. The implementation of an effective information literacy programme within the school curriculum was the goal of the study. A survey was distributed to 25 students in The Chinese High School in Singapore.